Alphonse Beaver interview - Beaver, Alphonse; Starr, David (Canadian Plains Research Centre, 1975)
8 p. transcript of an interview with Alphonse Beaver, conducted by David Starr on November 16, 1975. Tape number IH.254, transcript disc 30. Area of land covered by trapper, aged 74, in northern Alberta -- his life as a trapper, and working in Fort McMurray. Other no